Implementation of an adapted Safe Childbirth Checklist in rural Chiapas, Mexico: an evaluation study. (April 2017) - Molina, R; de Onis, J Villar; Reyes, A; Begley, M; Palazuelos, L; Elliott, P; Flores, H; Palazuelos, D
Abstract: Background: The Mexican Ministry of Health has advocated for increased skilled birth attendance in hospital facilities to decrease maternal and newborn morbidity and mortality. Partners In Health (PIH) works in a rural region of Mexico where the home birth rate is 60%. The primary purpose of this project is to improve the quality of care, including adherence to evidence-based practices and promotion of respectful practices during childbirth, in a rural hospital in Chiapas, Mexico. Additionally, we hope to strengthen the role of professional midwives and obstetric nurses as competent clinicians in managing women with low-risk pregnancies during childbirth. Methods: PIH collaborated with Ariadne Labs to adapt and implement the WHO Safe Childbirth Checklist in a rural hospital in Ángel Albino Corzo, Chiapas. Four pause points (at admission, just before delivery, within 1h of birth, and before discharge) were adapted according to the local context. Additional items were added to capture respectful practices during childbirth. We provided coaching training to the professional midwife and perinatal and obstetric nurses to make optimal use of the checklist for ongoing quality improvement in a team-based environment. The checklist and coaching tools have been developed into a mobile application using CommCare for instant data capture and continuous monitoring and evaluation. We used a mixed-methods study to capture adherence to evidence-based practices and integrated these findings with patient and provider experiences during labour and delivery. We conducted post-discharge surveys and post-partum interviews to explore how patients perceive the care they received during childbirth. Findings: By August, 2016, five obstetric nurses, one perinatal nurse, and one professional midwife were using the adapted Safe Childbirth Checklist in the study hospital. Data collection using CommCare began in September, 2016, and will continue until June, 2017. By March, 2017, we had captured data from about 350 birthing women using the WHO Safe Childbirth Checklist and 160 women who had completed the discharge survey. We have conducted interviews with 25 postpartum women and some of their birth companions. Data collection is ongoing but preliminary data from September to December, 2016, show that 64% (171/266) of women were asked at least two questions about their preferences in labour, 13% (28/216) of women received episiotomies without indication, 68% (147/216) initiated skin-to-skin within 1h of delivery, and 56% (122/216) of women initiated breastfeeding after delivery. Preliminary analysis of the discharge surveys reveal high satisfaction with the care women received at the hospital. Qualitative interviews indicate some variation in birth experiences. Interpretation: There is some variation in adherence with evidence-based practices and perceptions of good quality of care at the rural hospital since implementing the adapted Safe Childbirth Checklist along with other PIH-driven community initiatives. While we do not have a baseline for these indicators, our intervention represents the first attempt at any quality improvement initiative for childbirth care in this region, and adoption will require continued buy-in from hospital staff. Funding: The MacArthur Foundation, and Brigham and Women's Hospital Division of Women's Health.